Sistem Struk Transaksi Berbasis Mobile Pada Swalayan Meranti Kota Jambi - Kurniawan, Ilham Akbar; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2021)
MERANTI Jambi City supermarket, which was established in 2005, acts as a supermarket that sells basic food items (nine basic ingredients), food, drinks, milk, fruit, vegetables, baby equipment, clothing, household items, lights and electronics as well as furniture. MERANTI Supermarkets have 121 employees with 44 cashiers, counting 4 people and admin getting 3 people. MERANTI Supermarkets operating hours start at 09.00 WIB until 21.00 WIB. Advances in technology and science are a challenge for all supermarkets and shops in Indonesia, one of which is the MERANTI supermarket. The problem related to supermarkets is that the transaction place which is the proof of shopping still uses paper as the medium. In order for this problem to be resolved, a prototype design is needed to make it easier for programmers to make the application. This research produces a Mobile-based prototype design that describes how the application actually runs.